2012
DOI: 10.1111/j.1600-0854.2012.01361.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with a Kinesin‐2 Tail Propels Choline Acetyltransferase Flow Towards Synapse

Abstract: Bulk flow constitutes a substantial part of the slow transport of soluble proteins in axons. Though the underlying mechanism is unclear, evidences indicate that intermittent, kinesin based movement of large protein-aggregates aids this process. Choline acetyl-transferase (ChAT), a soluble enzyme catalyzing acetylcholine synthesis, propagates towards synapse at an intermediate, slow rate. The presynaptic enrichment of ChAT requires heterotrimeric kinesin-2, comprising KLP64D, KLP68D and DmKAP, in Drosophila. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 51 publications
3
31
0
Order By: Relevance
“…The latter is implicated in the assembly of T-bars marked by Bruchpilot at the presynaptic compartment (Tsurudome et al, 2010). The observed increase in the ChAT enrichment at the neuropile, which is transported by Kinesin-2 (Sadananda et al, 2012), is also consistent with this hypothesis. Further, the contents of the nascent Rab4-associated vesicles could regulate the membrane recycling at the nerve termini.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The latter is implicated in the assembly of T-bars marked by Bruchpilot at the presynaptic compartment (Tsurudome et al, 2010). The observed increase in the ChAT enrichment at the neuropile, which is transported by Kinesin-2 (Sadananda et al, 2012), is also consistent with this hypothesis. Further, the contents of the nascent Rab4-associated vesicles could regulate the membrane recycling at the nerve termini.…”
Section: Resultssupporting
confidence: 84%
“…4H–J; S3, Movie S4A). Previous reports showed that the KLP64DΔT forms a functional heterotrimeric motor complex (Sadananda et al, 2012). The presence of KLP64DΔT-GFP marginally improved the anterograde traffic as compared to the homozygous Klp64D −/− background.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FRAP kymographs indicate that both kinesin‐2 and tubulin are transported in the ciliary outer segment in a non‐particulate form. A similar recovery pattern was observed for the choline acetyltransferase in the axon . The latter directly binds to the C‐terminal tails of the kinesin‐2α subunit.…”
Section: Discussionmentioning
confidence: 94%
“…Terada et al injected a bolus of fluorescently-labeled creatine kinase (a soluble protein conveyed in SCb) into the squid giant axon, and saw a slow anterogradely-biased movement of the labeled protein population at rates reminiscent of SCb (Terada et al, 2000, 2010). Using a drosophila model, Sadananda et al have also recently shown a kinesin-dependent slow, anterogradely-biased flow of the soluble protein choline acetyltransferase in axons (Sadananda et al 2012). Thus it appears that the biased flow of cytosolic cargoes in slow axonal transport is a conserved phenomenon, and collective efforts in different model-systems should provide clarity of underlying mechanisms in the future.…”
Section: Cargoes Moving In Fast and Slow Axonal Transportmentioning
confidence: 99%